Seismic Monitoring of CO2 Geosequestration in Otway Basin, Australia - Urosevic, Milovan; Shulakova, V.; Pevzner, Roman; Kepic, Anton (EAGE, 2010)
CO2CRC Otway Project is the Australia s first demonstration of the deep geological storage of CO2. CO2 has been injected in a depleted gas field at the depth of 2050 m and then will be injected in saline aquifer at the depth of around 1 km. For time lapse studies, we had four different 3D seismic surveys available. Besides of a large 3D seismic volume acquired in the year 2000 prior gas production of the reservoir, three sequential 3D surveys were acquired at the same site but over a smaller area: baseline survey in 2008 and two monitoring surveys in 2009 and 2010. We concentrated on repeatability of 4D seismic data acquisition and processing. This led us to the results which allow to define CO2 location in the reservoir and proves that time-lapse seismic is a valuable tool in CO2 monitoring even in on-shore case.